A cross cultural study on expressing satisfaction in American English and Vietnamese - Nguyễn, Thị Thùy Linh (University of Languages and International Studies, 2017)
Based on the theoretical background of cross- cultural communication, this study aims at investigating the similarities and differences in expressing satisfaction towards different co- interactants in the Vietnamese and American language and culture. It fo (...)